ANALISIS VENTILASI ALAMIAH UNTUK MODIFIKASI RUMAH KACA STANDARD PEAK TIPE CURAM - Herry Suhardiyanto; Meiske Widyarti; Fiendy Chrisfian; Iin Sundani Muliawati (PERTETA, 2006)
ABSTRACT In tropical region, greenhouses are built to protect plant from heavy rain and insects. However, climatic conditions in the tropics are often ignored by greenhouse designers. In such hot and humid environment, antural ventilation is the most important factors to be considered. There is no cost required to operate the natural ventilation, but it needs an accurate openings design. This paper deals with a modification analysis of the steep-type standard peak greenhouse where inside air temperature was very high. A computer program has been developed to calculate neutral pressure plane and natural ventilation rate. It was used in simulation to predict natural ventilation rate in five alternatives of modified and two alternatives of newly designed greendhouse. An alternative of modified greenhouse design was selected according to the highest natural ventilation rate at the lowest cost. Keyword: